Noninvasive brain oxygen saturation measurement during caloric response in vertigo patients—preliminary report - Nowaczewska, Magdalena; Marzec, Maria; Kluczyński, Łukasz; Sierakowska, Katarzyna; Wróbel, Maciej (Frontiers in Neurology, 2025)
IntroductionAlthough videonystagmography (VNG) is a useful test for evaluating patients with vestibular symptoms, it may cause undesirable side effects. The aim of this study was to measure cerebral tissue oxygen saturation in patients with vertigo undergoing VNG and assess its relationship with clinical parameters, including the severity of the procedure-related side effects.Materials and methodsContinuous measurement of regional oxygen saturation (rSO2) from both hemispheres during VNG with caloric stimulation was performed in patients with chronic vertigo using a near-infrared spectroscopy sensor. This sensor, connected to a regional oximetry system (O3™, Masimo, Irvine, CA), was placed on the participant’s forehead. During and after the VNG procedure, patient-perceived dizziness, discomfort, headache, and nausea—side effects related to VNG testing—were assessed using a 0-to-10 visual analog scale (VAS).ResultsA total of 23 patients were enrolled, with a mean age of 54.27 years and an average duration of vertigo of 5.96 years. Of these, 11 patients experienced VNG-related side effects. No significant differences in oximetry parameters were observed before and after the caloric test, regardless of whether cold or hot water was used or whether the left or right ear was stimulated. We found a positive correlation between the overall change in oxygenation values in both hemispheres during the whole VNG test (delta) and the severity of side effects symptoms (VAS). The correlation coefficient between delta and VAS was higher in the right hemisphere than in the left (accordingly 0.69 vs. 0.62, p < 0.05).ConclusionCaloric stimulation does not influence regional brain oxygenation as measured by a regional oximetry system. However, fluctuations in rSO2 values during the whole VNG procedure, predominantly on the right side, may be associated with the side effects of the procedure.